THE ROLE OF LINGUISTIC LANDSCAPE IN SUPPORTING INCLUSIVE EDUCATION: A SYSTEMATIC LITERATURE REVIEW (2020-2025) - Ni Luh Eka Setyawati; Made Hery Santosa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
Linguistic landscape is commonly found in public spaces through signs, information, boards, posters, directional signs, and other visual displays. In the context of education, these displays become part of students’ daily learning experiences and may influence how they interact with their surroundings. Previous studies have discussed linguistic landscape in relation to multilingualism and language learning. However, its role in supporting inclusive education has receive less attention. This study aims to explore how lingusitic landscape supports inclusive education based on studies published between 2020 and 2025. A systematic literature review was chosen using the PRISMA framework. Ten articles were selected based on inclusion criteria and analyze the contribution of linguistic landscape to inclusive educational practices. The results show that linguistic landscape supports inclusive education in several ways. It reflects inclusive values and policies within educational settings, improves accessibility through visual, tactile, and navigational resources. these findings suggest that linguistic landscape can be used as a resource to create learning environments that are more inclusive, assessible, and responsive to the needs of diverse learners.